Chemical dissection of hormone signalling in arabidopsis - Jackson, Robert (2014)
The plant hormone gibberellin (GA) regulates many developmental processes during a plant’s life cycle, including root and hypocotyl growth. Bioactive GAs promote GA-responsive growth and development by targetting DELLA proteins for degradation. Whilst the early steps of GA signalling are well understood it is not yet clear how the DELLA proteins alter the expression of GA-responsive genes. As other steps of the signalling pathway are encoded by multi-gene families it is possible that genetic redundancy is masking the transcription factors that act downstream of DELLAs. Using a chemical screen based on DELLA protein’s control of GA biosynthesis, 28 chemicals which blocked the GA-mediated downregulation of GA20ox1::GUS activity were identified. Using GA-mediated RGA degradation as a marker, 11 chemicals were identified as acting downstream of DELLAs in the GA signalling pathway.